Room temperature Co-doped manganite/graphene sensor operating at high pulsed magnetic fields - Lukose, Rasuole (Sci Rep, 2019)
The demand to increase the sensitivity to magnetic field in a broad magnetic field ranges has led to the research of novel materials for sensor applications. Therefore, the hybrid system consisting of two different magnetoresistive materials – nanostructured Co-doped manganite La(1−x)Sr(x)(Mn(1−y)Co(y))(z)O(3) and single- and few-layer graphene – were combined and investigated as potential system for magnetic field sensing. The negative colossal magnetoresistance (CMR) of manganite-cobaltite and positive one of graphene gives the possibility to increase the sensitivity to magnetic field of the hybrid sensor. The performed magnetoresistance (MR) measurements of individual few layer (n = 1–5) graphene structures revealed the highest MR values for three-layer graphene (3LG), whereas additional Co-doping increased the MR values of nanostructured manganite films. The connection of 3LG graphene and Co-doped magnanite film in a voltage divider configuration significantly increased the sensitivity of the hybrid sensor at low and intermediate magnetic fields (1–2 T): 70 mV/VT of hybrid sensor in comparison with 56 mV/VT for 3LG and 12 mV/VT for Co-doped magnanite film, respectively, and broadened the magnetic field operation range (0.1–20) T of the produced sensor prototype.